2021
DOI: 10.3174/ajnr.a7201
|View full text |Cite
|
Sign up to set email alerts
|

Time Course and Clinical Correlates of Retinal Diffusion Restrictions in Acute Central Retinal Artery Occlusion

Abstract: BACKGROUND AND PURPOSE: Retinal diffusion restrictions were recently identified as a regular finding in acute central retinal artery occlusion. We sought to investigate the influence of technical MR imaging and clinical parameters on the detection rate of retinal diffusion restrictions on standard brain DWI. MATERIALS AND METHODS:In this retrospective cohort study, MR imaging scans of patients with central retinal artery occlusion were assessed by 2 readers for retinal diffusion restrictions on DWI performed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
1
14
1
Order By: Relevance
“…This retrospective investigation of 85 patients is the first to confirm the presence of RDR in patients with BRAO on routine stroke DWI–MRI, although overall sensitivity, as well as interrater and intrarater reliability were lower than previously reported for complete CRAO 5 , 9 . The findings of our study are well conceivable, because the area of retinal ischemia in BRAO is generally smaller when compared to complete CRAO and may show considerable variability ranging from hemicentral RAO (caused by occlusion of one of the two main divisions of the CRA at the optic disc) to small, circumscribed lesions, e. g. in peripapillary BRAO.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…This retrospective investigation of 85 patients is the first to confirm the presence of RDR in patients with BRAO on routine stroke DWI–MRI, although overall sensitivity, as well as interrater and intrarater reliability were lower than previously reported for complete CRAO 5 , 9 . The findings of our study are well conceivable, because the area of retinal ischemia in BRAO is generally smaller when compared to complete CRAO and may show considerable variability ranging from hemicentral RAO (caused by occlusion of one of the two main divisions of the CRA at the optic disc) to small, circumscribed lesions, e. g. in peripapillary BRAO.…”
Section: Discussioncontrasting
confidence: 46%
“…In ischemic stroke, a high signal on DWI with low ADC is generally observed within the first week after symptom onset 14 . Interestingly, Danyel et al reported decreased detection of RDR for complete CRAO in DWI performed after the first week 9 . Our study did not find differences in RDR detection rates among time interval groups in BRAO patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the fourth patient presented with vision loss of the right eye with fundoscopic examination revealing retinal edema with cherry red spot sign indicative of central retinal artery occlusion. Although retinal restricted diffusion of the right eye was in accordance with a diagnosis of CRAO 32,33 , DWI further revealed right-sided optic nerve restricted diffusion of the intraorbital portion suggesting concurrent PION (Fig. 3D).…”
Section: Diffusion Weighted Mr Imaging Analysismentioning
confidence: 69%
“…Cerebral DWI has long been an established method to identify ischemic stroke, which is a feared complication in GCA patients with cranial artery involvement 48 . However, a growing number of case reports [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]49 and systematic studies 26,32,33,50,51 substantiate the presence of DWI abnormalities in non-arteritic ischemic lesions of the optic nerve and retina. Additionally, DTI studies by Fang and Wang et al have observed changes in ON fractional anisotropy in subacute AION of unspecified etiology 52,53 .…”
Section: Discussionmentioning
confidence: 99%